Aesthetic Representation of Sufi Femininity: Women’s Costumes and Symbolism in Wayang Wali and Wayang Sambung - Lutfianto; Abdul Munip; Maharsi (ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin, 2025)
This article examines the aesthetic representation of female characters in Wayang Wali by Ki Sunan Sunhaji and Wayang Sambung by Ki Muhammad Mukti as part of the Islamic cultural da’wah strategy in Java. Drawing on visual semiotics, the analysis focuses on the depiction of female figures through physical appearance, ornaments, costumes, and bodily expressions as interconnected systems of cultural signs. The findings indicate that the representation of women in Wayang Wali and Wayang Sambung deliberately avoids sensuality and luxury, instead emphasizing simplicity, modesty, and spiritual values aligned with Islamic teachings. Elements such as soft color tones, modest clothing, and restrained bodily expressions are employed to construct an idealized image of femininity grounded in Sufi philosophy and Javanese-Islamic ethical principles. Women are represented not as objects of desire, but as symbolic figures embodying grace, humility, and spirituality. In conclusion, the visual aesthetics of female characters in these wayang traditions demonstrate a unique synthesis of religious values, local cultural identity, and artistic expression. As forms of cultural representation, Wayang Wali and Wayang Sambung function not only as artistic media but also as significant instruments of Islamic cultural transmission, offering an alternative model of beauty and femininity rooted in ethical and spiritual ideals.